The Relationship between Albumin Levels with SGOT, SGPT, and de Ritis Ratio in Chronic Hepatitis B Patients: A Single-Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Nursasmi, Ami Tri; Zelly Dia Rofinda; Desywar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Chronic hepatitis B (CHB) is a persistent hepatitis B virus (HBV) infection and can cause progressive liver damage. This damage can be measured through a decrease in albumin levels and an increase in liver enzymes such as aspartate aminotransferase (AST/SGOT), alanine aminotransferase (ALT/SGPT), and de Ritis ratio (AST/ALT). This study aims to analyze the relationship between albumin levels and SGOT, SGPT, and de Ritis ratio in CHB patients. Methods: This cross-sectional retrospective analytical study involved 50 CHB patients diagnosed at Dr. M. Djamil General Hospital Padang between June 2022 to June 2023. Data on albumin levels, SGOT, SGPT, and de Ritis ratio were obtained from medical records. The de Ritis ratio, SGOT, and SGPT were grouped into normal and increased. Statistical analysis used an independent t-test with a significance of p < 0.05. Results: The research subjects consisted of 26 men (52%) and 24 women (48%) with an average age of 42.46 ± 13.39 years. The mean albumin level in the increased SGOT group (3.69 ± 0.78 g/dL) was significantly lower than the normal SGOT group (4.39 ± 0.61 g/dL) (p = 0.003). The mean albumin level in the increased de Ritis ratio group (3.90 ± 0.80 g/dL) was also significantly lower than the normal de Ritis ratio group (4.46 ± 0.70 g/dL) (p = 0.006). There was no significant difference between albumin levels in the normal and increased SGPT groups (p = 0.548). Conclusion: There is a significant negative relationship between albumin levels and SGOT and de Ritis ratio in CHB patients. Decreased albumin levels may be an indicator of more severe liver damage in these patients.